2022
DOI: 10.1108/jgr-10-2021-0082
|View full text |Cite
|
Sign up to set email alerts
|

Does corporate social responsibility affect dividend policy? Empirical evidence in the French context

Abstract: Purpose The purpose of this paper is to focus on the impact of corporate social responsibility (CSR) on dividend policy in the French context. In addition, the authors seek to determine if the individual components of CSR influence dividend policy. Design/methodology/approach This study uses panel data methodology for a sample of French non-financial firms between 2008 and 2018. Generalized least squares method is used to estimate the models. Findings Using panel data methodology for a sample of 825 observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 100 publications
2
10
0
Order By: Relevance
“… Cheung et al (2018) and Ni and Zhang (2019) discovered that CSR had a positive impact on the dividend pay-out ratio but no significant impact on the propensity to pay dividends for US-listed businesses. More recently, Salah and Amar (2022) also provide evidence of positive impact of CSR practices on dividend policy in the French setting and found that individual dimensions of CSR have a positive relationship with a dividend pay-out. Contrarily, Saeed and Zamir (2021) found a negative relationship between CSR and dividend pay-out in emerging markets and owed the negative association with the higher institutional ownership and funding of growth opportunities.…”
Section: Related Literature and Hypotheses Developmentmentioning
confidence: 95%
“… Cheung et al (2018) and Ni and Zhang (2019) discovered that CSR had a positive impact on the dividend pay-out ratio but no significant impact on the propensity to pay dividends for US-listed businesses. More recently, Salah and Amar (2022) also provide evidence of positive impact of CSR practices on dividend policy in the French setting and found that individual dimensions of CSR have a positive relationship with a dividend pay-out. Contrarily, Saeed and Zamir (2021) found a negative relationship between CSR and dividend pay-out in emerging markets and owed the negative association with the higher institutional ownership and funding of growth opportunities.…”
Section: Related Literature and Hypotheses Developmentmentioning
confidence: 95%
“…Thus, a financial conflict may arise between meeting societal needs through CSR initiatives and compensating shareholders with dividend payments. Consistent with this view, recent studies have questioned how the business orientation towards CSR goals affects dividend payouts, but the findings remain divided (Ellili, 2022;Fonseca & Richardson, 2023;Ni & Zhang, 2019;Niccolò et al, 2020;Oh & Park, 2021;Salah & Amar, 2022;Verga Matos et al, 2020;Zahid et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has questioned how the business orientation toward ESG goals affects corporate dividends distributions, with conflicting findings: a positive relationship between ESG scores and a firm's capacity to pay dividends (Benlemlih, 2019;Verga Matos et al, 2020;Ould Daoud Ellili, 2022;Salah & Amar, 2022). However, other studies revealed a negative association (Cheung et al,2018;Ni & Zhang, 2019;Niccolo et al, 2020)…”
Section: -Introductionmentioning
confidence: 99%